Post 2015: what can be learnt from the impact of health performance on donor policies for health assistance? - Katharina M.K. Stepping (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
It is unclear how health will be positioned in the post-2015 development agenda. Health already plays a dominant role in the Millennium Development Goals (MDGs). Likewise, funding for health has risen considerably since 1990. For the design of a future agenda, it is important to understand the motives for the provision of health assistance and whether health MDGs have had an impact on health aid. The key results are: The decision about which country to select and how much health assistance to allocate is the result of a manifold process. Health conditions in the recipient country are one aspect. Other determinants are foreign policy motives, concerns about corruption, donor preferences for health and strategic interactions among donors. The average donor prefers to financially support the fight against HIV/AIDS. A high HIV prevalence rate substantially increases the selection probability of a potential aid recipient and the allocation of health aid. Either donors are more sensitised about HIV/AIDS or they consider other health problems as being less important. As attention and funds are directed to HIV/AIDS, concerns about maternal or child health are crowded out. Child mortality and maternal mortality rates matter only for the selection decision. A high under-five mortality rate slightly increases the selection chance. A high maternal mortality rate, however, has a significantly negative effect on the selection probability. The definition of health objectives at the international level, represented in three MDGs, has not provoked any change in the decision pattern of the average donor for health assistance. At the individual level, no two donor countries follow exactly the same pattern in their decision-making process. Yet, the decision to allocate health aid is unrelated to the health performance in the recipient country in most cases. Contrary to expectations based on common beliefs in the aid literature, like-minded donors are not more strongly focused on health performance when deciding on health assistance. In light of the debate about the post-2015 development agenda, the question is whether these health indicators are appropriate parameters. The results illustrate that even a policy in strict accordance with health performance could be argued as not being well-targeted health aid. First, many causes or multipliers are found outside the health sector such as lack of education. Second, the indicators child mortality and maternal mortality only document the (final) extreme event. The future development agenda should be moulded in such a way that linkages between health and other sectors can be taken into account. It should also focus on measuring the quality of health and health care. The interdependencies – in particular the direction of causal relationships – need to be better understood. Particularly the request for global goals would require a clear understanding of the driving factors for good health performance at different stages of development.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen